The Effectiveness of Role-Playing Games in Enriching Vocabulary and Reducing Anxiety in English Language Learning - Melisa Khoyyiroh Harahap; Diah Khoirunnisa Harahap (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2025)
This study aims to examine the effectiveness of Role-Playing Games (RPG) as a pedagogical intervention in improving English vocabulary mastery (cognitive domain) and simultaneously reducing foreign language anxiety (FLA) (affective domain) in elementary school students. Anxiety is a significant barrier to language acquisition. The study used a quasi-experimental pretest-posttest control group design. The study population consisted of sixth-grade elementary school students in Medan, with a sample of N=60 divided into an Experimental Group (using scenario-based RPG) and a Control Group (using conventional methods: drill and memorization). The intervention was conducted over eight weeks. Anxiety was measured using the Modified Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire (Likert scale), and vocabulary was measured using a pretest-posttest objective test. Data analysis used ANCOVA (Analysis of Covariance) to control for initial scores. The results showed that RPG significantly increased vocabulary acquisition (p<0.001) and significantly reduced Foreign Language Learning Anxiety (p=0.005) compared to the control group. It was concluded that RPG is a holistic method that successfully creates a safe learning environment (low-anxiety environment) while providing an authentic context for vocabulary application and retention in elementary school students.